2021
DOI: 10.1002/rth2.12602
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factor IX‐Fc fusion protein in severe hemophilia B: Patient‐reported outcomes and health‐related quality of life

Abstract: Introduction In 2017, all people with severe hemophilia B in Ireland switched to recombinant factor IX Fc fusion protein concentrate (rFIXFc) prophylaxis. Patient‐reported outcomes (PROs) and health‐related quality of life (HRQoL) are important to evaluate with new treatments. Aims To assess HRQoL in people with severe hemophilia B and their experience after switching to rFIXFc prophylaxis. Methods Participants completed a Patient Reported Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Although this was not evaluated in the current study, previous real-world data have shown adherence to be an important consideration when physicians consider switching patients to rFIXFc [ 25 ], and that adherence rates improve after switching [ 17 , 19 ]. Other previously published real-world data have shown that rFIXFc may help to improve QoL, not only as consequence of a reduced treatment burden but also by reducing pain and improving activities of daily living [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this was not evaluated in the current study, previous real-world data have shown adherence to be an important consideration when physicians consider switching patients to rFIXFc [ 25 ], and that adherence rates improve after switching [ 17 , 19 ]. Other previously published real-world data have shown that rFIXFc may help to improve QoL, not only as consequence of a reduced treatment burden but also by reducing pain and improving activities of daily living [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials evaluate drugs in an environment that controls for external ‘real-life’ factors and, as such, are limited by, for example, restrictions in the study population and mandated dose/treatment intervals. Data on the real-world effectiveness and usage of rFIXFc prophylaxis in a clinical setting are beneficial to add to the evidence from clinical trials in routine clinical practice, and a number of real-world evaluations of rFIXFc have been performed [ 13 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…51 Patients who switch to rFIXFc also experience improvements in quality of life, mood, activities of daily living, physical functioning, social functioning, and pain, which are limited in patients who remain on SHL therapy. 44,47 It is possible, although very rare, for inhibitor development to occur in a patient switching to rFIXFc prophylaxis, as reported in an isolated case study of an 82-year-old man with severe hemophilia B switching from SHL rFIX prophylaxis (see Supporting Information for further details). 57…”
Section: Switchingmentioning
confidence: 99%
“…1 Multiple papers have described outcomes among patients who switched to rFIXFc prophylaxis, with very consistent findings in clinical trials and in real-world clinical settings (Table S2). 11,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Typically, patients switching to rFIXFc prophylaxis experience reductions in injection frequency: the most common post-switch rFIXFc dose interval is 7 days, but intervals of 10 or 14 days are also seen. 11,42,43,45,46,[49][50][51][53][54][55][56] Factor consumption is also reduced after switching, generally by 26%-50%, to around 40-60 IU/kg/week.…”
Section: Switchingmentioning
confidence: 99%
See 1 more Smart Citation